The triple burden of undernutrition: prevalence and parental determinants among Indonesian school-aged children from coastal areas - Lolita, Lolita; Sultan, Cindy Elsandra; Kurniawan, Alvin; Ihsana, Nuni; Nur Aisyah, Fatma; Ikhsanudin, Azis; Osman, Ahmed Mohamed Yehia (Asian Conference on Clinical Pharmacy (ACCP), 2025)
Background: Children's malnutrition remains a significant issue within national health concern across Indonesia. The triple burden of undernutrition, comprising stunting, wasting dan underweight, increases children's susceptibility to illness and mortality. This study examines the prevalence of stunting, wasting and underweight, while identifying parental determinants linked to undernutrition prevalence among school-aged children living in coastal areas at Indonesia Methods: An analytical cross-sectional was conducted among elementary school children aged 7 to 8 years and their parents in coastal areas of Sijuk District, Bangka Belitung Province. Data on the children participants’ age, weight, height, were collected, as well as WHO AnthroPlus software to compute anthropometric data. Quantitative data gathering tool on the parental determinants by using semi-structured questionnaires. Data analysis used were the Chi-Square and Fisher test to analyse significant determinant of stunting, wasting and underweight. Results: This study included 39 respondents based on eligibility criteria. The prevalence of stunting, wasting and underweight about 10,3%, 17,9%, and 23,1%, respectively. Most of the undernutrition children had fathers who worked as fishermen (59%), while the mother as a housewife (92.3%) with educational background of junior high school (38.5%). Mothers receiving iron, folic acid and zinc during pregnancy about 92.3%, 89.7%, and 79.5%. The family's income is generally below the minimum wage (71.8%) with good nutritional upbringing, good housing and family environmental sanitation, as well as easy access to health services. In the group of parental respondents, 51,3% demonstrated a high level of knowledge regarding undernutririon, and 53.8% of parents exhibit a high level of knowledge regarding the use of supplementation during pregnancy. This study also indicated a significant correlation between parental knowledge of supplementation towards the prevalence of wasting (p=0.015), as well as between parental knowledge related undernutrition towards the prevalence of underweight among school-aged children in coastal areas (p=0.031). Conclusions: The prevalence of wasting and underweight remains above the target established by the Indonesian Ministry of Health, which is 14%. Parental determinants, including knowledge of supplementation, significantly correlate with the prevalence of wasting, whereas knowledge of undernutrition significantly correlate with the prevalence underweight among school-aged children in coastal regions.